PENGARUH SEMANGAT KERJA PEGAWAI TERHADAP MINAT BACA MASYARAKAT PADA KANTOR ARSIP DAN PERPUSTAKAAN DAERAH KOTA TERNATE. - Nurlaila Nurlaila (Jurnal Manajemen Sinergi, 2014)
This study aims to analyze and determine the effect the morale of the publicinterest which occurred in the Office of Archives and Library area of Ternate,carried out using quantitative research methods. In particular the implementation of the Library experiencing empty or decrease in public interest.Based on the research results, public interest is affected by this employee morale can be folded on the magnitude of the coefficient of determination (r) of 0.224, this figure shows that employee morale can influence society's interest in readingis 22.4%, and the remaining 77.6% influenced by other variables not examined in this study. hypothesis test results are known t of 7.128 at sig t of 0.002 at significance level alpha (α = 0.05). it is stated that morale has significant influence on society reading interest, meaning that the hypothesis is proven and accepted. Based on research results is expected that the leadership of the Regional Office of Archives and Library of Ternate, should motivate employees about the importance of the information available at the Regional Library. Keywords : Semangat kerja, Minat Baca Masyarakat